Indexing Process in Research using Verbal Protocol - Tolare, Jessica Beatriz [UNESP]; Fujita, Mariângela Spotti Lopes [UNESP] (Nomos Verlag, 2024)
The Verbal Protocol is an introspective technique that allows one to observe the strategies, difficulties, and procedures during the execution of a certain. Aiming at investigating the use of the introspective technique named Verbal Protocol in studies carried out to analyze the indexing process, the systematic literature mapping method was adopted. Nineteen theses and dissertations were analyzed. The results showed that the research addressed different theoretical aspects in their studies and observed combinations of the Verbal Protocol with other techniques. Verbal Protocol provided insights into both the positive and negative perspectives of the indexer, as well as the context in which they operate.